IDDF2020-ABS-0157 Therapeutic effect of dietary n-3 polyunsaturated fatty acid in Crohn's disease by restoring Th17/Treg imbalance through PPAR-r/AMPK/ACC mediated pathway. (18th November 2020) - Yao, Jiayin; Hu, Bang; Sun, Jiachen; Zhi, Min
Abstract : Background: Effective treatments of Crohn's disease (CD) are limited. Diet is not only an environmental factor in the pathogenesis of CD but also an underlying therapeutic target. Our previous study confirmed the protective effect of dietary n-3 polyunsaturated fatty acid (n3-PUFA) in CD rats without mechanisms explored in-depth. In this study, we aimed to investigate and validate the mechanisms of n-3PUFA in CD in vivo and vitro focusing in T cell differentiation and immune disorder. Methods: Experimental CD-like colitis rats were induced by 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) and naïve T cells were isolated from colonic mucosa lamina propria. Disease active index (DAI), Colon macroscopic damage index (CMDI), Tissue damage index (TDI) scores, weights, colon length and histologic manifestation were evaluated. Ratio of T helper cell type 17 (Th17)/regulatory T cells (Treg), expressions of differentiation-associated transducer and cytokines were detected. Relationship between Th17/Treg and peroxisome proliferator-activated receptor-r (PPAR-r)/adenosine monophosphate-activated protein kinase (AMPK)/acetyl CoA carboxylase (ACC) signal pathways were analyzed. Results: Dietary n-3PUFA attenuated CD rats by reducing DAI, CMDI, TDI scores and colon shortening, promoted weight gain, and ameliorated histologic manifestations. N-3PUFA shifted Th17 into Treg by activating PPAR-r and downstream AMPK, while inhibiting ACC. Effect of restoring imbalance of Th17/Treg could be enhanced by PPAR-r agonist rosiglitazone, AMPK agonist AICAR and ACC antagonist TOFA, inhibited by PPAR-r antagonist GW9662, AMPK antagonist compound C and ACC agonist citric acid. Conclusions: Dietary n-3PUFA effectively protected and ameliorated CD. The underlying mechanisms involved the restoration of Th17/Treg imbalance by regulating PPAR-r/AMPK/ACC signal pathways. (Figure 1 ).